THE PLAGUE BETWEEN THE MEDITERRANEAN AND THE PACIFIC MOCHE. Of seas, ships and merchants. (By the way Covid 19): De mares, navíos y mercaderes. (A propósito del Covid 19) - JACINTO PAZOS, Pedro (2020)
The assumption that we are trying to interpret is that the world in which we live is governed by parameters that nature determines and also conditions. Although, nature is the pantry of human survival, from its flora and fauna (and its seas), these can also be part of its extinction. And the plagues or pandemics in the world have proved. All viruses have been generated in animals or plants that man has not been able to handleand, conversely, has manipulated and destroyed them. Human trust in animal life as part of its physiological conservation can also be reversed and can be exterminated. Furthermore, when it comes to hegemonic economic structures and, where the sense of inequality and conflict between man and nature and, between men themselves, remain unchanged. The marine merchants made their journey in the different seas and with it the capital, the shipwreck and the plagues. It is therefore a question of observing a parallel from the Black Death that happened in Europe in the fourteenth century and, what is described in northern Peruvian Mochica, at the beginning and middle of the twentieth century.